2018
DOI: 10.1007/s11661-017-4446-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of the Heat-Affected Zones in Grade 92 Steel Welds: Double-Pass and Multipass Welds

Abstract: The microstructure in the heat-affected zone (HAZ) of multipass welds typical of those used in power plants and made from 9 wt pct chromium martensitic Grade 92 steel is complex. Therefore, there is a need for systematic microstructural investigations to define the different regions of the microstructure across the HAZ of Grade 92 steel welds manufactured using the traditional arc welding processes in order to understand possible failure mechanisms after long-term service. In this study, the microstructure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
5
26
1
Order By: Relevance
“…In previous studies of 9% Cr steels, the use of ion beam induced SE imaging has been used successful in the quantitative analysis of M 23 C 6 carbides [51][52][53]. In the 9% Cr MarBN steel being analysed in this study, this technique was again capable of differentiating the relatively larger M 23 C 6 carbides (Fig.…”
Section: Microstructural Characterisation Of Creep Exposed Materialsmentioning
confidence: 73%
“…In previous studies of 9% Cr steels, the use of ion beam induced SE imaging has been used successful in the quantitative analysis of M 23 C 6 carbides [51][52][53]. In the 9% Cr MarBN steel being analysed in this study, this technique was again capable of differentiating the relatively larger M 23 C 6 carbides (Fig.…”
Section: Microstructural Characterisation Of Creep Exposed Materialsmentioning
confidence: 73%
“…To communicate the needs to the larger community regarding relevant assessment of 9% Cr CSEF steels, and in particular weldments in the as-fabricated and post-test evaluation, a number of recent manuscripts have sought to provide a more accurate description for the HAZ (Table 3) (Refs. 5,6), relevant cross-weld creep test parameters and geometries (Refs. 7,8), macro-assessment of weldments in the as-fabricated and post-test conditions (subject of this manuscript), and micro-assessment of weldments in the as-fabricated and post-test conditions (Refs.…”
Section: Otz (Overtempered Zone)mentioning
confidence: 99%
“…microstructure across the HAZ as a function of the welding process [6,7]. e microstructure in the HAZ of a single-pass, bead-on-plate weld on a Grade 92 parent was systematically investigated by using an extensive range of advanced electron and ion-microscopy-based techniques [6].…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…It was found that the microstructure in the HAZ should be categorized in terms of the dissolution and transformation behavior as a function of a decreasing peak temperature during welding. e three primary microstructural regions, shown schematically in Figure 3, were defined as follows [6,7]: (a) e completely transformed (CT) region, in which the original matrix is completely reaustenitized with complete dissolution of the preexisting secondary precipitate particles. e time at peak temperature is typically sufficient to dissolve inclusions present in the base steel.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation